Determination of cadmium, lead and copper in clarias gariepinus from mass market / Nur Syafiqah Fauzan - Fauzan, Nur Syafiqah (2014)
Introduction: Living organisms required variety of heavy metals. Fish has been the main supply of inexpensive and healthy protein to a huge percent of the human population. Marine fish or aquaculture fish have the potential to accumulate the heavy metals. Excessive amount of heavy metal may give a health risk effect. Methodology: A cross-sectional study was done using 150(n) sample of African catfish bought from various places in Selangor. Sample preparations are using dry ash techniques. Sample analysis is using Atomic Absorption Spectrophotometer (AAS). Questionnaires were distributed among catfish purchaser for demographic data. Heavy metal concentrations were compared using One Way ANOVA (SPSS v.18). Results: The results demonstrate the presence of Cd, Pb and Cu concentrations inside the Clarias gariepinus. The mean concentration of Cd was 0.060 mg/kg, Pb was 0.195 mg/kg and Cu was 2.554 mg/kg. Generally, the concentration of Cd , Pb and ·cu were ranging from O to 0.232, 0.004 to 0.736 and 0.332 to 6.072. The health risk assessment was conducted for both male and female. Hazard Index obtained from three studied heavy metal were below than one (Hl<1). Conclusion: In a conclusion, overall concentration of Cd, Pb and Cu were lower than national and international standards. However, only Pb concentration was slightly higher than European Community Standard. After the health risk assessment was conducted to each three studied heavy metals, the consumer in Selangor area were safely consume the African catfish (Clarias gariepinus).